The Impact of Employee Networks and Organizational Culture on Innovation Performance - Bou Rached, Nicole (2022)
In today’s competitive business environment, innovation has become a necessity for organizations to survive and achieve strategic objectives. To this end, the growing body of research has concentrated on the role of policies, resources and technologies in shaping innovation, with little attention on how the social fabric of employee relationship and prevailing cultures impact innovation. Therefore, the aim of this study is two-fold: (1) to examine the impact of employees’ social network structure, position and ties on their innovation capability and (2) to explore variances in innovation capability across different organization cultures, namely adhocracy, clan, market and hierarchy. To do so, a questionnaire was used to collect data from 111 employees working across different firms where they were asked to report on the patterns of their relationships with other employees and to assess the prevailing culture. Social network analysis was conducted using E-NET, followed by a hierarchical multiple regression which showed that employees’ network density, degree centrality and constraint are positively associated with innovation capability, with education level moderating these relationships. Moreover, it was shown that adhocracy and hierarchy cultures are associated with innovation capability. The findings are important for both managers and policy makers to improve innovative capabilities by restructuring employee relationships and supporting specific cultures.